KONTROVERSIAL TOKOH JAYABHAYA DALAM MASYARAKAT JAWA - Suyanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
This article is the result of contemplation about the phenomena that occur in today’s society. In this millennial era, it seems that many people believe in controversial things, one of which is Jangka Jayabaya which is famous as a prophecy of the times. This is a challenge for the academic community therefore, the author tries to straighten out the information that is “konon” (supposedly) with the method of observation of various library references. The results of the observations obtained, both from historical records, ancient literary works, legends of the Javanese kingdom era, and journal articles in the mass media, show that the name Jayabaya in the book entitled Jangka Jayabaya is not the name of Jayabaya, the king of the Kadiri Kingdom as referred to in the historical facts of the Javanese kingdom.